PENGARUH MOTIVASI BELAJAR DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR PENGANTAR EKONOMI MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI INSTITUT PENDIDIKAN TAPANULI SELATAN T.A 2024/2025 - Hartini, Sri; Siregar, Rosnida; Ritonga, Mariyatul Kubtiyah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to know the describe of the influence of learning motivation and learning discipline on the learning outcomes of students of the Economics Education Study Program, South Tapanuli Education Institute, Academic Year 2024/2025. This study was conducted by using descriptive quantitative method. This research was conducted at the South Tapanuli Education Institute. The population was all first-year students of the Economics Education Study Program, South Tapanuli Education Institute, Academic Year 2024/2025, totaling 230 students. The sampling technique was carried out by purposive sampling of 26 students. The data collection method used a questionnaire. Based on the calculation results, the average of student learning motivation was 84.50 in the very good category, the average of student learning discipline was 81.11 in the very good category, and the average of introductory economics learning outcomes was 85.31 in the very good category. Based on the results of statistical processing, it was obtained F-calculated = 14.732 > F-table = 1.711 or a significance score was less than 0.05 (0.000 <0.05). Based on the results of the comparison of these scores, the alternative hypothesis is accepted or agreed upon together. This means that there is any significant influence of learning motivation and learning discipline on the learning outcomes of students of the introduction to economics of the Economics Education Study Program, Tapanuli Selatan Institute of Education, Academic Year 2024/2025.